Molecular identification of blaTEM and blaCTX-M genes in multidrug-resistant Escherichia coli found in milk samples from dairy cattle farms in Tulungagung, Indonesia - Widodo, Agus; Lamid, Mirni; Effendi, Mustofa Helmi; Tyasningsih, Wiwiek; Raharjo, Dadik; Khairullah, Aswin Rafif; Kurniawan, Shendy Canadya; Yustinasari, Lita Rakhma; Riwu, Katty Hendriana Priscilia; Silaen, Otto Sahat Martua (Journal of veterinary research, 2023)
Escherichia coli is an opportunistic bacteria that can grow easily, produce toxins, and resist antibiotics. The phenomenon of E. coli developing multidrug resistance is currently the subject of extensive research. The objective of this study was to molecularly identify blaTEM and blaCTX-M genes in multidrug-resistant E. coli found in milk samples from dairy cattle farms in Tulungagung, Indonesia.One hundred and ten milk samples were collected from 45 dairy cattle farms in Tulungagung, Indonesia. Indole, methyl red, Voges–Proskauer and in citrate tests and triple iron sugar agar tests were used to identify E. coli. Multidrug resistance was determined in isolates through antibiotic sensitivity tests using tetracycline, streptomycin, trimethoprim, chloramphenicol and aztreonam. Extended-spectrum beta lactamase enzyme production was confirmed by double-disc synergy test (DDST). Molecular identification was performed to confirm the blaTEM and blaCTX-M genes.One hundred and one (91.82%) E. coli strains were isolated from the samples. The antibiotic sensitivity test showed four (3.96%) multidrug-resistant (MDR) and one (0.99%) ESBL-positive E. coli by DDST confirmation. There were three (77.78%) blaTEM genes and one (0.99%) blaCTX-M gene discovered in the MDR E. coli isolates using PCR for molecular identification.The findings of the blaTEM and blaCTX-M genes encoding ESBL E. coli in dairy cattle milk in Tulungagung, Indonesia is concerning and argues for prompt action to stop the emergence of antibiotic resistance which has an impact on public health.